Flowers of Galilee: The Collected Essays of Israel Shamir by Israel Shamir (Tempe, Arizona: Dandelion Books, 2004. 304 pages.) (American Journal of Islam and Society, 2004)
Flowers of Galilee breaks new ground in modern political discourse. Thisbook recommends a democratic one-state solution in all of historicalPalestine and the return of the Palestinians to rebuild their villages. Thebeautiful front cover painting by Suleiman Mansour of Jerusalem lovinglydepicts a Palestinian family, children seated on a donkey, walking past a hillcovered with olive trees. Similarly, Israel Shamir’s essays portray the peaceful,pastoral landscape of the Holy Land and the humanity of its inhabitants,juxtaposed against the ugliness and inhumanity of Jewish racism.These thought-provoking essays, written in Jaffa during the al-AqsaIntifada in 2001-02, call for Jews to leave their sense of exclusivity andplead for human equality. The author, a Russian immigrant to Israel in 1969,followed his meditations to their inevitable conclusion, renounced Judaism,and was baptized in the Palestinian Orthodox Christian Church ofJerusalem. A brilliant storyteller with a vast knowledge of history, he discussescurrent events and their global implications with brutal honesty andtenderness. His clear insights and lyrical use of language to illustrate social,religious, and political complexities make him the Khalil Gibran of our time.An important chapter, “The Last Action Heroes,” memorializes theSpring 2002 siege of Bethlehem. The Israeli army surrounded 40 monksand priests and 200 Palestinians seeking refuge in the Church of Nativity.For a month, “people starved ... Stench of corpses and of infected woundsfilled the old church” (p. 63). The UN did nothing, but a few InternationalSolidarity Movement activists from America and Europe, including theauthor’s son, broke the siege. One group distracted the soldiers while theothers rushed into the church’s gates, brought food and water, and helpednegotiate a surrender.Shamir deconstructs the legal fictions of the state of Israel and the elusivePalestinian state: “Israelis who would like to live in peace with theirPalestinian neighbors ... cannot counteract the raw muscle of the AmericanJewish leadership” (p.179). He further dissects the Jewish Holocaust cultand other Zionist public relations tactics. He exposes the two-state solutionas a political bluff, calls on the world to cut off aid to Israel, and admonishesthe Muslim world for indulging in usury ...